1995
DOI: 10.1302/0301-620x.77b1.7822371
|View full text |Cite
|
Sign up to set email alerts
|

Role of melatonin deficiency in the development of scoliosis in pinealectomised chickens

Abstract: We studied the possible role of melatonin deficiency in experimentally-induced scoliosis. A total of 90 chickens underwent pinealectomy on the third day after hatching: 30 were treated with serotonin, 30 with melatonin and 30 received no therapy (control group). Scoliosis developed in all the control group, in 22 of the serotonin group, and in only 6 of the melatonin group. The six melatonin-treated chickens with scoliosis had less severe spinal deformities than those in the serotonin-treated group. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
4
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 0 publications
3
125
4
4
Order By: Relevance
“…Recently, Bagnall et al [2] also reported that the production of a scoliotic curvature in young chickens was not affected by MLT administration after pinealectomy. These results are in sharp contrast to those reported by Machida et al [19,21], who designed a similar study and found that pineal gland transplantation and MLT therapy following pinealectomy procedure prevented the development of spinal deformity. The reason for the differences between these two studies is not obvious, and such a confusing disparity warrants additional study.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Recently, Bagnall et al [2] also reported that the production of a scoliotic curvature in young chickens was not affected by MLT administration after pinealectomy. These results are in sharp contrast to those reported by Machida et al [19,21], who designed a similar study and found that pineal gland transplantation and MLT therapy following pinealectomy procedure prevented the development of spinal deformity. The reason for the differences between these two studies is not obvious, and such a confusing disparity warrants additional study.…”
Section: Discussioncontrasting
confidence: 98%
“…Conversely, the results show that scoliosis was observed in 58% and 50% of groups B and C, respectively. Although Machida et al [19,20,21,23] have reported that 100% of their pinealectomized chickens developed a scoliotic curve, these results have not been confirmed in other studies [1,2,3,9,14,30,33,34]. Recently, a 52% incidence of scoliosis after pinealectomy was reported by Wang et al [34], and this is confirmed by the results of our current study.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations